AN ANALYSIS OF PHRASAL VERBS FOUND IN PREMISE JOURNAL OF ENGLISH EDUCATION STUDY PROGRAM OF MUHAMMADIYAH UNIVERSITY OF METRO VOLUME 8 NUMBER 1 2019 - Aryani, Putri (Journal of English Education and Enterpreneurship (JEEP), 2021)
This descriptive qualitative research was aimed to (1) Explain how the phrasal verbs distribute to the text; (2) Calculate the number and percentages of the phrasal verbs found in the text. The subject of this research was PREMISE Journal of English Education Study Program of Muhammadiyah University of Metro Volume 8 Number 1. Afterward, the object of this research was the phrasal verbs which found in abstracts of PREMISE Journal. The data were collected by observing the journal which consisted of several phrasal verbs. After that, the collected data were analyzed by identifying, categorizing and calculating the data. Eventually, the result shows that not all types of phrasal verbs available in the abstracts. The total numbers of phrasal verbs in the abstract were 37; consist of 28 non-separable types and 20 transitive types. Then, the percentages from each type shows 28 times or 76% for non-separable type and transitive type arise 20 times or 54.1%. The researcher did not found transitive and separable type in the text. Lastly, the researcher concluded that the dominant phrasal verb in the text is non-separable phrasal verb.